Correction: Incidence, clinical course and risk factor for recurrent PCR positivity in discharged COVID-19 patients in Guangzhou, China: A prospective cohort study. - Jiazhen Zheng; Rui Zhou; Fengjuan Chen; Guofang Tang; Keyi Wu; Furong Li; Huamin Liu; Jianyun Lu; Jiyuan Zhou; Ziying Yang; Yuxin Yuan; Chunliang Lei; et al. (PLoS Neglected Tropical Diseases)
[This corrects the article DOI: 10.1371/journal.pntd.0008648.].